Advancing Humanitarian Supply Chains: A Scoping Review of Challenge - Che Hassan, Muhammad Hamdi (Unisia, 2025)
Global disasters present a significant threat to human civilisation. Disasters can be categorised as natural (severe rainfall, avalanches, earthquakes) or cause by human (industrial accidents, chemical leaks, structural failures). The distribution of relief and recovery resources during and after the crisis mitigates the suffering of victims. The humanitarian supply chain is crucial in such circumstances. Humanitarian supply chains are crucial for providing lifesaving assistance during catastrophes and emergencies, although they function under extremely demanding conditions. This scoping study examines the existing scholarly literature on humanitarian supply chains, particularly in Asia, to outline the current landscape of research and explore where future scholarly attention might be directed. This study identified six primary topics and twenty sub themes concerning challenges in the context of humanitarian supply chains. The primary themes encompass Data Collection Challenges, Transportation Constraints, Bureaucratic Delays, Security Risks, Collaboration, and Cultural Sensitivity. The analysis suggests that most studies focus on comprehending the direct effects on humanitarian supply systems. This indicates that the field is primarily oriented toward solving immediate, practical problems faced by responders in the aftermath of a crisis. This scoping review analysis is pertinent to individuals engaged in public crisis management, including local authorities, public entities, emergency services, and non-governmental organisations participating in humanitarian assistance.